Existence of solutions for a nonlinear elliptic Dirichlet boundary value problem with an inverse square potential - Yongqing Li; Shenghua Weng (Boundary Value Problems, 2006)
Via the linking theorem, the existence of nontrivial solutions for a nonlinear elliptic Dirichlet boundary value problem with an inverse square potential is proved.